Necessidades formativas de professores alfabetizadores dos anos iniciais: caminhos da práxis à tomada de consciência - Rosa, Ana Cláudia Kogake de la (2021)
This research, with a qualitative approach, had as general objective to identify and analyze the education training needs highlighted by literacy teachers for the development of training processes. Based on the general objective, the following specific objectives were listed: I – to know which aspects of the Teachers’ Training Center´s Education Training Meetings were highlighted by literacy teachers as significant, or not, considering their practice; II – to analyze the challenges indicated by literacy teachers who participated in the of the Teachers’ Training Center´s Education Training Meetings in relation to their practice in the classroom; III – to develop a training proposal for literacy teachers in an educational network. The conduct of this research was justified by the studies that evinced a concentration of research which had the focus on evaluating the quality of education training programs for literacy teachers and a lower concentration in relation to research aimed at the education training needs of these teachers, from the background from which these needs emerged. The theoretical framework which substantiated the developed topics were: continuing education (IMBERNÓN, 2011); schoolcentred education training (IMBERNÓN, 2011; ALARCÃO, 2011; CANÁRIO, 1998); education training needs, main topic of this research (LOPEZ, 2017; RODRIGUES, 2016; ESTRELA; LEITE, 1999), and literacy – literacy teachers’ education training (FERREIRO, 2011; 2013; SOARES, 2011). The research subjects were literacy teachers who participated in the Teachers’ Training Center´s Education Training Meetings in an educational network. The data collection was conducted by questionnaires applied to the total group of teachers who took part in the trainings in 2019 and by interviews done with six literacy teachers of this group. The data analysis was based on the Analysis of Prose (ANDRÉ, 1983) and was able to identify the education training needs of a literacy teachers group, to point out constitutive aspects of the education trainings’ meetings shown as significant and to indicate an education training proposal for literacy teachers of the analyzed education network. The results corroborated the research that point to the analysis of education training needs as a powerful strategy for change in practice and the training of critical and reflective teachers and made it possible to highlight the lack of research related to the training of literacy teachers who work in rural areas. They also pointed out the relevance of the trainer deepening studies on strategies for analyzing the education training needs of teachers, which are important for these professionals to become aware of their training needs in praxis. Finally, this study strengthened the importance that education training proposals for literacy teachers prioritize the exchange of experiences as a way of identifying training needs, respecting the context from which they emerge and aiming at changes in practice